Pola Sebaran Retensi dan Ketersediaan Hara pada Toposekuen Lahan Jagung di Desa Pilolaheya, Kabupaten Bone Bolango: Distribution Patterns of Retention and Nutrition Availability at Maize Land Toposequens in Pilolaheya Village, Bone Bolango Regency - Nurdin Kyai Baderan; Nangsi Ismail; Fitriah Suryani Jamin (Universitas Hasanuddin, 2022)
Information on land quality as the basis for land management in maize cultivation at the site level is very important, but generally not always available. Study aimed to determine the distribution pattern of nutrient retention and availability in Pilolaheya Village, Bone Bolango Regency. This study used soil survey and deskwork methods to analyze data of nutrient retention (organic C-OC, pH, base saturation-BS, cation exchange capacity-CEC), total N, P2O5, and K2O for nutrient availability. The result shows that the distribution pattern of nutrient retention in corn topose sequences for soil pH on the lower slopes, base saturation on the lower and middle slopes tended to increase with soil depth, while soil pH on the upper slopes, OC and BS on the upper slopes tended to be the opposite., while the soil pH on the middle slope, OC on the lower and middle slopes, and the CEC of all slopes tended to be irregular with the depth of the soil. The distribution pattern of nutrient availability for Total N on the lower and middle slopes, and P2O5 on all slopes tends to be irregular with soil depth, while the total N on the upper slope tends to decrease with soil depth, while the distribution pattern of K2O on the middle and upper slopes tends to be the same, but inversely proportional to the distribution pattern on the downslope